The Effectiveness of Quick Response Code Indonesian Standard (QRIS) in Increasing MSME Transactions at Car Free Day in Merdeka Square, Medan - Tyus Windi Ayuni; Ibrahim Mallam Fali; Rahima Br Purba; Amin Hou; Adi Harianto (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2026)
This study aims to analyze the effectiveness of the use of the Quick Response Code Indonesian Standard (QRIS) in creasing MSME transactions at Car Free Day in Lapangan Merdekea, Medan City. The independent variables in this study are the ease use of QRIS and trust in the use of QRIS, while the dependent variable is the increase in MSME transactions. This study is motivated by the development of digital technology, which has encouraged the transformation of non-cash payment systems in the MSME sector. Although QRIS has been widely adopted, several obstacles still exist, such as limited techonological understanding and low levels of trust in digital payment systems. This study employed a quantitative research method with an associative approach. The population consisted of all culinary business actors at Car Free Day in Lapangan Merdeka, Medan City. The sampling technique used purposive sampling with a total 45 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modelling (SEM) based on Smart PLS. the results indicate that the ease of use of QRIS has a positive and significant effect on increasing MSME transactions, with a path coefficient value of 0.612 an a p-value of 0.000. trust in the use of QRIS also has a positive and significant effect on increasing MSME transactions, with a path coefficient value of 0.684 and a p-value of 0.000. Furthermore, the ease of use and trust in the use of QRIS simultaneously enhance the effectiveness of MSME transactions at Car Free Day in Lapangan Merdeka, Medan City. This study shows that the ease of use and trust in QRIS are important factors in increasing the adoption of digital payments among MSMEs. The use of QRIS provides convenience, security, transcation efficiency and supports the digital transformarion of MSMEs in the digital economy era.